2006
DOI: 10.1007/s11270-005-9022-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oxygen Demand (COD) Reduction in Domestic Wastewater by Fly Ash and Brick Kiln Ash

Abstract: The potential of fly ash, brick kiln ash and commercial activated carbon is determined for the reduction of chemical oxygen demand (COD) from domestic wastewater. Laboratory experiments are conducted for investigating the effect of treatment time, adsorbent dose, pH of the media, initial COD concentration, agitation speed and particle size of adsorbents on the COD reduction from the domestic wastewater. Starting with an initial COD concentration of 1080 mg/l the maximum COD reduction achieved for fly ash was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 7 publications
3
26
0
Order By: Relevance
“…Adsorption-based technique Devi and Dahiya 2006) developed with low-cost carbonaceous materials showed good potential, more so for chemical oxygen demand (COD) removal from domestic wastewater. Such adsorption approach can offer an easy and economic solution to these environmental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption-based technique Devi and Dahiya 2006) developed with low-cost carbonaceous materials showed good potential, more so for chemical oxygen demand (COD) removal from domestic wastewater. Such adsorption approach can offer an easy and economic solution to these environmental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that removal efficiencies for organic compounds increase with decreasing of the sorbents particle size [3][4][5]. In this experiment (Fig.…”
Section: Effect Of Wood Fly Ash Particle Sizementioning
confidence: 54%
“…5). The ''n'' value of 0.14 (as 1/n equal to 7.31) was low in comparison to ''n'' values obtained with sorption of COD by commercial AC, which is usually reported within the range of 2.5-1.0 [2,3,34]. Although the low value of ''n'' indicates that the wood ash tested had less affinity to adsorbe the organic pollutants in the wastewater treated, 37% of average COD removal efficiency at 160 mg L À1 of wood ash was achieved.…”
Section: Effect Of Wood Fly Ash Particle Sizementioning
confidence: 61%
See 1 more Smart Citation
“…Evidently, the COD reduction can only be proceeded via the photocatalytic oxidation so that more active sites of the SACPs are advantageous to the oxidation reaction. 34) As for different SACP in Fig 8, the removal percentage of COD is relatively lower for COP samples due to the greater competition of the intermediates for the oxidative species. From Fig.…”
Section: Cod Effect Of Sacpsmentioning
confidence: 84%